(untitled) (Tribhuvan Journal, 2025)
This article examines ecological ethics in selected Jātaka tales through a Buddhist narrative approach to environmental thought. It addresses a gap in Buddhist environmental studies: doctrinal interpretations of interdependence, compassion, and non-harming are often prioritized over narrative forms that shape ethical imagination and ecological consciousness. This study employs qualitative and thematic analysis of five Jātaka tales: Ruru, Nigrodha-Miga, Mahā-Mora, Vattaka, and Kumbha - using E. B. Cowell’s translation as the primary source. The analysis draws on Buddhist environmental philosophy and the works of contemporary scholars such as Joanna Macy, Mary Evelyn Tucker, Stephanie Kaza, and David R. Loy. The findings show that the selected narratives consistently articulate ecological ethics through recurring principles: interspecies compassion, ethical leadership, foresight and restraint, cooperative interdependence, and critique of greed. Across the texts, environmental disruption is linked to moral and cognitive failure, while ecological stability emerges through virtuous relational conduct. The study argues that the Jātaka tales construct a relational ecological worldview where sustainability is inseparable from ethical transformation. They function as narrative frameworks for ecological consciousness, demonstrating that environmental thought in the Buddhist tradition is fundamentally ethical, relational, and pedagogical.